Birth Weight and Preterm Delivery Outcomes of Perinatally vs Nonperinatally Human Immunodeficiency Virus-Infected Pregnant Women in the United States: Results From the PHACS SMARTT Study and IMPAACT P1025 Protocol. (30th May 2017) - Jao, Jennifer; Kacanek, Deborah; Williams, Paige L; Geffner, Mitchell E; Livingston, Elizabeth G; Sperling, Rhoda S; Patel, Kunjal; Bardeguez, Arlene D; Burchett, Sandra K; Chakhtoura, Nahida; Scott, Gwendolyn B; Van Dyke, Russell B; et al.
Summary: Overall lack of association between maternal perinatal human immunodeficiency virus (HIV) infection and preterm delivery or infant birth weight (BW) is reassuring. The higher rates of low BW observed in older women with perinatally acquired HIV may warrant further investigations. Abstract: Background: Pregnancy outcomes of perinatally human immunodeficiency virus–infected women (PHIV) are poorly defined. Methods: We compared preterm delivery and birth weight (BW) outcomes (low BW [LBW], <2500 g), small-for-gestational-age [SGA], and BW z scores [BWZ]) in HIV-exposed uninfected infants of PHIV vs nonperinatally HIV-infected (NPHIV) pregnant women in the Pediatric HIV/AIDS Cohort Study Surveillance Monitoring of ART Toxicities or International Maternal Pediatric Adolescent AIDS Clinical Trials P1025 studies. Mixed effects models and log binomial models were used to assess the association of maternal PHIV status with infant outcomes. Age-stratified analyses were performed. Results: From 1998 to 2013, 2270 HIV-infected pregnant women delivered 2692 newborns (270 born to PHIV and 2422 to NPHIV women). PHIV women were younger, (mean age 21 vs 25 years, P < .01) and more likely to have a pregnancy CD4 count <200 cells/mm3 (19% vs 11%, P = .01). No associations between maternal PHIV status and preterm delivery, SGA, or LBW were observed. After adjustment, BWZ was 0.12 lower in infants of PHIV vs NPHIV women (adjusted mean, −0.45 vs −0.33; P = .04). Among women aged 23–30 years (n = 1770), maternal PHIV was associated with LBW (aRR = 1.74; 95% confidence interval, 1.18, 2.58; P < .01). Conclusion: The overall lack of association between maternal PHIV status and preterm delivery or infant BW outcomes is reassuring. The higher rates of LBW observed in PHIV women aged 23–30 years warrants further mechanism-based investigations as this is a rapidly growing and aging population worldwide. Clinical Trials Registration: PHACS SMARTT study, NCT01310023. Clinical Trials Registration: IMPAACT 1025, NCT00028145.